Etika Kerja Islami sebagai Moderasi Pengaruh Manajemen SDM Terhadap Kepuasan Kerja Dosen - Idarianty Idarianty; Dewanti Apriliana; Bunga Permata Sari; Witdia Witdia (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the influence of Human Resource Management (HRM) on Lecturer Job Satisfaction and examine the role of Islamic Work Ethics (EKI) as a moderating variable. Job satisfaction is a crucial factor influencing lecturer retention and performance quality, which is directly influenced by HRM practices in the institution. However, the context of Islamic institutions suggests that internal values ​​(EKI) may influence how HRM practices are perceived. This quantitative study used a survey approach with respondents [State the number/type of respondents, e.g.: 120 permanent lecturers] from [State the type of institution, e.g.: Private Islamic Religious College]. Data were analyzed using Moderated Regression Analysis (MRA). The results showed that: (1) HRM practices have a positive and significant influence on Lecturer Job Satisfaction. (2) Islamic Work Ethics are proven to moderate (strengthen/weaken) the influence of HRM on Lecturer Job Satisfaction. These findings indicate that internalization of Islamic values ​​in work is a key variable that determines the effectiveness of HRM programs and the achievement of optimal job satisfaction in Islamic academic environments. Managerial implications suggest the integration of EKI into the institution's entire HRM process